Fermi‐Level Pinning Free High‐Performance 2D CMOS Inverter Fabricated with Van Der Waals Bottom Contacts. (30th March 2021) - Ngo, Tien Dat; Yang, Zheng; Lee, Myeongjin; Ali, Fida; Moon, Inyong; Kim, Dong Gyu; Taniguchi, Takashi; Watanabe, Kenji; Lee, Kang‐Yoon; Yoo, Won Jong
Abstract: Effective control of 2D transistors polarity is a critical challenge in the process for integrating 2D materials into semiconductor devices. Herein, a doping‐free approach for developing tungsten diselenide (WSe2 ) logic devices by utilizing the van der Waals (vdWs) bottom electrical contact with platinum and indium as the high and low work function metal respectively is reported. The device structure is free from chemical disorder and crystal defects arising from metal deposition, which enables a near ideal Fermi‐level de‐pinning. With effective controllability of device polarity through metal work function change, a complementary metal‐oxide‐semiconductor field effect transistor inverter with a gain of 198 at a bias voltage of 4.5 V is achieved. This study demonstrates an ultrahigh performance 2D inverter realized by controlling the device polarity from using Fermi‐level pinning‐free vdWs bottom contacts. Abstract : Fermi level de‐pinning is observed with top gate WSe2 field‐effect transistors by utilization of van der Waals bottom contact. From that approach, a doping‐free complementary metal‐oxide semiconductor inverter with ultra‐high gain is developed.